Effect of different environments, grafting methods and times on sprouting, graft success and plant growth of walnut (Juglans regia) - AHMED, N; SINGH, S R; SRIVASTAVA, K K; SHAGOO, P A; HAYAT, SHAZIA (The Indian Journal of Agricultural Sciences, 2013)
To find out the ideal factors which affect the graft success of walnut, an experiment was carried out at experimental farm of Central Institute of Temperate Horticulture during 2008-2009 with three environmental conditions (open field, polytrench and polyhouse), two grafting methods (wedge grafting and tongue grafting) and four grafting times (15 February, 1 March, 15 March and 1 April ). Polyhouse recorded highest percentage of sprouting (65.51 %), graft success (54.46 %) and plant growth (168.75 cm). Wedge grafting was found superior to tongue grafting in respect of sprouting percent (62.22 %), graft success (52.45 %) and plant height (151.5 cm). Amongst the grafting times 15 March recorded the highest graft success (58.00 %) and plant growth (163.78 cm). The highest sprouting (80.00 %) and graft success (64.62 %) was found under polyhouse with wedge grafting performed on 15 of March under Kashmir conditions can be adopted for mass multiplication.